Addendum to: Qualitative aspects of solutions in resonators - Quintanilla, R.; Racke, R. (Archives of Mechanics, 2011)
In correcting a small mistake in [10], we can prove a new result on nonexponential stability for a coupled system arising in resonators. This also gives another (surprising and simple) example for a thermoelastic system changing from exponential stability to non-exponential stability, when changing from Fourier’s law to Cattaneo’s law in modeling of the heat conduction.